PENGARUH PERMAINAN TARGET TERHADAP KETEPATAN BACKHAND SERVICE BULUTANGKIS PESERTA EKSTRAKURIKULER BULUTANGKIS DI SMP NEGERI 8 MAKASSAR (Studi Eksperimen Pada Siswa Ekstrakulikuler SMP Negeri 8 Makassar) - Kurniawan, Irvan; Cakrawijaya, Muhammad Hidayat (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi STKIP Mega Rezky Makassar, 2018)
This research aims to figure out the effect of target games to the accuracy of backhand service on the participants of badminton extracurricular in SMP Negeri 8 Makassar. This research is an experimental research with one group pretest-posttest design with 12 times treatment. The subjects of this research are the participants of badminton extracurricular in SMP Negeri 8 Makassar for about 22 students. Service ability is measures by instrument of backhand service ability in James Poole’s book (1986:24). The data is analyzed by using t-test analysis and it is tested before for normality and homogeneity in advance. Based on the analysis of the research result and discussion, it is obtained the value of tcount at 18.585 with a significance value at 0.000. Mean value of pretest result is 12.82 and the mean value of posttest result is increase up to 20.05.